2015
DOI: 10.1021/acsami.5b05344
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dielectric Properties of PVDF Composites by Employing Surface Modified Strong Polarized BaTiO3 Particles Derived by Molten Salt Method

Abstract: BaTiO3/polyvinylidene fluoride (BT/PVDF) is the extensive reported composite material for application in modern electric devices. However, there still exists some obstacles prohibiting the further improvement of dielectric performance, such as poor interfacial compatibility and low dielectric constant. Therefore, in depth study of the size dependent polarization and surface modification of BT particle is of technological importance in developing high performance BT/PVDF composites. Here, a facile molten-salt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
189
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(194 citation statements)
references
References 72 publications
5
189
0
Order By: Relevance
“…The obtained maximum ε r is comparable and relatively higher than values by various synthesis methods (eg, sol‐gel, hydrothermal, pechini, mechanochemical, precipitation, and oxalate coprecipitation) reported in Refs . All of dielectric loss measured at 10 3 Hz result in lower than 0.033 as shown in Figure B, which is desired value for application because of low energy loss …”
Section: Resultssupporting
confidence: 65%
“…The obtained maximum ε r is comparable and relatively higher than values by various synthesis methods (eg, sol‐gel, hydrothermal, pechini, mechanochemical, precipitation, and oxalate coprecipitation) reported in Refs . All of dielectric loss measured at 10 3 Hz result in lower than 0.033 as shown in Figure B, which is desired value for application because of low energy loss …”
Section: Resultssupporting
confidence: 65%
“…The dielectric result confirmed that the 77.5 ± 2.5 nm of BaTiO 3 powder product was still in stabilized ferroelectric phase at room temperature, which agrees well with the XRD and DSC results. On the other hand, a lower tan δ of the bulk specimen is required for dielectric device applications because of the low heat produced [51]. According to the dielectric data, the measured dielectric permittivity of the specimen was found to be~53 for 100 Hz, and it decreased slightly to~51 and~50 by increasing the frequency from 1 to 10 kHz.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…High‐dielectric‐constant (high‐ε) polymer‐matrix composites are attractive materials owing to their important applications in the solid‐state energy storage field, (eg, the embedded capacitors) . With the aim to achieve high energy storage densities, a great effort has been made to enhance the dielectric constant (ε) of the composites . There are two types of high‐ε composites, depending on the improvement methodology used.…”
Section: Introductionmentioning
confidence: 99%